Study of acid properties of new polymeric complexes of maleic acid polymethylvinyl ether cross-linked by polypropylene glycol - Sarsenbekova, A.Zh.; Khalitova, A.I.; Klimova, T.E.; Khamitova, T.O.; Kudaibergen, G.K.; Figurinene, I.V.; Medeshova, A.T.; Sotchenko, R.K. (KSU publ., 2020)
Dissociation course of polymethylvinyl ether of maleic acid cross-linked by polypropylene glycol (PMVE-MA with PPG) was investigated using classical potentiometric titration and colloid titration. It is assumed, that in the course of colloid titration monovalent counter-ions are replaced by the oppositely charged polycation, therefore it was determined the general concentration of anionic groups of hydrogel of polymethylvinyl ether of maleic acid cross-linked by polypropylene glycol. The apparent constant of dissociation (pseudo constant of dissociation) depends on the forming of the polyelectric complex but does not depend on the degree of dissociation. While it is known that potentiometric titration are determined by the apparent constant of dissociation that decreased simultaneously with the increase of the dissociation degree. Protons releasing from acid groups of hydrogel of polymethylvinyl ether of maleic acid cross-linked by polypropylene glycol leads to the formation of the complex with stronger cationic polyelectrolyte. Therefore, comparison of the results of potentiometric and colloid titration makes it possible to take in the information about the interrelation of acid characteristics of the surface of PMVE-MA with PPG and its functional properties. As a result we can define its application area for creation of new high-efficient composite material.
Keywords: polyelectrolyte; colloid titration; potentiometric titration; dissociation; hydrogel